2000
DOI: 10.1074/jbc.275.7.4827
|View full text |Cite
|
Sign up to set email alerts
|

ERO1-L, a Human Protein That Favors Disulfide Bond Formation in the Endoplasmic Reticulum

Abstract: Oxidizing conditions must be maintained in the endoplasmic reticulum (ER) to allow the formation of disulfide bonds in secretory proteins. Here we report the cloning and characterization of a mammalian gene (ERO1-L) that shares extensive homology with the Saccharomyces cerevisiae ERO1 gene, required in yeast for oxidative protein folding. When expressed in mammalian cells, the product of the human ERO1-L gene colocalizes with ER markers and displays Endo-H-sensitive glycans. In isolated microsomes, ERO1-L beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
231
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 273 publications
(235 citation statements)
references
References 38 publications
3
231
0
1
Order By: Relevance
“…Also, in this assay, the mobility shift induced by deglycosylation is greater for ERO1-L␤ than for ERO1-L␣. As previously observed for ERO1-L␣ translated in the presence of canine microsomal membranes (26), the electrophoretic mobility of the translocated and deglycosylated ERO1-L␣ is undistinguishable from that of the protein synthesized in the absence of membranes. This seems to be the case also for ERO1-L␤, suggesting that the leader peptides of the two human ERO1-L genes might not undergo cleavage.…”
Section: Two Distinct Ero1-like Genes Are Present In Both Humansupporting
confidence: 53%
See 2 more Smart Citations
“…Also, in this assay, the mobility shift induced by deglycosylation is greater for ERO1-L␤ than for ERO1-L␣. As previously observed for ERO1-L␣ translated in the presence of canine microsomal membranes (26), the electrophoretic mobility of the translocated and deglycosylated ERO1-L␣ is undistinguishable from that of the protein synthesized in the absence of membranes. This seems to be the case also for ERO1-L␤, suggesting that the leader peptides of the two human ERO1-L genes might not undergo cleavage.…”
Section: Two Distinct Ero1-like Genes Are Present In Both Humansupporting
confidence: 53%
“…We showed that the products of the ERO1-L gene are able to complement several functions of the endogenous ERO1 in yeast, suggesting the existence of similar oxidative protein folding pathways in human and Saccharomyces cerevisiae (26).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…In S. cerevisiae, an additional protein, Erv2p, performs a similar function to that of Ero1 (4,5). Although orthologues of Erv2p do not seem to exist in higher eukaryotes, two human isoforms of Ero1 have been identified, Ero1␣ and Ero1␤ (6,7).…”
mentioning
confidence: 99%
“…39 Ero1-a is widely expressed, yet both isoforms have enzymatic activities that are controlled by regulatory disulfides formed among catalytic and non-catalytic cysteines to avoid futile oxidation cycles, which prevents excess hydrogen peroxide production. [40][41][42] PDI and Ero1 represent for the ER a feedback regulatory system that is able to sense and respond to different redox conditions. 43,44 The interplay between Ero1-a and PDI has been studied and some mechanical aspects are well characterized.…”
Section: Protein Disulfide Isomerases -Pdi'smentioning
confidence: 99%